Context-aware audit space management system / N. Omar, N. Zamani and R. Ghazali - Omar, N.; Zamani, N.; Ghazali, R. (Universiti Teknologi MARA, Perak, 2018)
This paper highlights the large demand issue of space usage in teaching and learning environment in Universiti Teknologi MARA (UiTM). The spaces usage in UiTM has raised serious concern due to the large of various type of working environment with dynamic number of workers and students. The space capacity with its related data are growing and most of the time requires real-time information access. As current process only can be done manually, providing comprehensive and accurate information about the teaching and learning spaces are quite limited. Therefore, this paper presents the design of a context-aware audit space management system that will provide a comprehensive space information at a real-time. This paper highlights the related of components in an automated space-time audit. The component based will be integrated and tested in the existing space management system.